Fabrication and Performance of Segmented Thermoplastic Composite Wind Turbine Blades - Garate, Juan; Solovitz, Stephen A.; Kim, Dave (International Journal of Precision Engineering and Manufacturing-Green Technology, 5(2), 2018)
Large-scale wind turbine blades exceed 50 m in length, and they are currently fashioned as single pieces. Along with the significant challenge of fabricating these blades, there is also an issue of transporting them to field sites, which can account for a substantial portion of the installation cost. Further, typical blades are produced from thermoset composite materials, which cannot be reused at the end of the turbine lifetime. Therefore, a new manufacturing process is developed, forming the blades in smaller segments that can be joined after transportation to the field. The process uses vacuum-assisted thermoforming of thermoplastic composites, which can be recycled after use. Six turbine blades were fabricated from two separate segments composed of two elements each, and they were joined using fusion welding and adhesives. A set of three blades was tested at a small-scale wind farm, producing power outputs on the order of 20 W at low wind speeds, comparable to an existing commercial turbine.